Reduning alleviates sepsis-induced acute lung injury by reducing apoptosis of pulmonary microvascular endothelial cells - Wang, Ziyi; Guo, Zhe; Wang, Xuesong; Liao, Haiyan; Chen, Feng; Liu, Yuxin; Wang, Zhong (Frontiers in Immunology, 2023)
Introduction Sepsis-induced acute lung injury (SALI) is a critical illness with high mortality, and pulmonary microvascular endothelial cells (PMECs) barrier dysfunction is a well-documented pathogenesis of SALI. The current study aimed to investigate the underlying mechanism of Reduning (RDN) in the treatment of SALI. Methods Network pharmacology and molecular dynamics simulation (MDS) were used to confirm the possibility of key active components of RDN combining with AKT1. Hematoxylin-eosin staining (HE) and immunohistochemistry (IHC) were used to investigate the effect of RDN in vivo. Immunofluorescence (IF) and co-immunoprecipitation (CoIP) were used to investigate the relationship between mammalian target of rapamycin (mTOR) and Bax in PMECs. ELISA was used to test the level of TNF-α. Flow cytometry was used to detect apoptosis. JC-1 and electron microscopy were used to evaluate mitochondrial damage. The results showed that RDN likely alleviated SALI via targeting AKT1. Results In vivo, RDN could evidently decrease the expression levels of apoptosis-related proteins, alleviate mitochondrial damage, reduce lung tissue edema, down-regulate the level of TNF-α in the serum, and improve the mortality of sepsis in mice. In vitro, RDN had a significant effect on reducing the level of apoptosis-related proteins and cell apoptosis rate, while also mitigated mitochondrial damage. Furthermore, RDN could effectively lower the level of Bax in PMECs and increase the level of mTOR both in vivo and in vitro. Notably, mTOR has the ability to directly bind to Bax, and RDN can enhance this binding capability. Discussion RDN could attenuate SALI through reducing apoptosis of PMECs, which is a promising therapeutic strategy for SALI prevention.